1998
DOI: 10.1046/j.1469-8137.1998.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar radiation on the endemic Mediterranean red alga Rissoella verruculosa: photosynthetic performance, pigment content and the activities of enzymes related to nutrient uptake

Abstract: The effects of full‐spectrum solar radiation and of solar radiation deprived of total u.v. radiation (λ<395 nm) on the endemic Mediterranean red alga Rissoella verruculosa (Bertoloni) J. Agardh were studied in situ in early summer, from sunrise to sunset. Photosynthetic performance, pigment content and the activities of enzymes related to nutrient uptake, were monitored under both radiation conditions throughout a daylight period. The doses of solar radiation, measured on the day during which the experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 49 publications
1
28
0
8
Order By: Relevance
“…Nevertheless, none of these last species have been found (e.g. Posidonia oceanica, Cystoseira spinosa), with the exception of Rissoella verruculosa, a mediolittoral species that does not appear in our sublittoral samples, but which is present in La Herradura (Flores-Moya et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, none of these last species have been found (e.g. Posidonia oceanica, Cystoseira spinosa), with the exception of Rissoella verruculosa, a mediolittoral species that does not appear in our sublittoral samples, but which is present in La Herradura (Flores-Moya et al, 1998).…”
Section: Discussionmentioning
confidence: 92%
“…Photoinhibition has been proposed as a strategy for photoprotection against high irradiance (Hanelt 1998). Several studies focusing on the effects of natural UVR on the photosynthetic performance of macroalgae from high exposure environments have revealed that the occurrence of photoinhibition under high solar radiation depends basically on daily changes in the level of irradiance, algal position on the shore, vertical light attenuation, or a combination of all these factors , Flores-Moya et al 1998.…”
Section: Dynamic Photoinhibition: Effects Of Par and Uvrmentioning
confidence: 99%
“…In plants, pigments of the photosynthetic apparatus can also be destroyed by UV exposure (Strid et al 1990), with the phycobilins being the most sensitive, and carotenoids generally being less affected than the chlorophylls (Teramura 1983; Hä der and Hä der 1989). As a consequence of a number of molecular effects, several physiological processes are impaired, such as photosynthesis (Bornman 1989;Strid et al 1990;Nogues and Baker 1995;Allen et al 1997), and nutrient uptake (Dö hler 1985(Dö hler , 1992Flores-Moya et al 1998;Gó mez et al 1998), while others, e.g., respiration, appear to be less affected (Larkum and Wood 1993;Aguilera et al 1999). Photosynthesis is probably the most intensively studied process in plant biology.…”
Section: Biological Effects Of Uvbmentioning
confidence: 99%